Research on the spatial state and electrical distance variation of overhead transmission lines with changes in foundation - Shuai Wang; Xiaokai Meng; Siqing Xu; Zhumao Lu; Yang Bai (AIP Advances)
This article conducts a thorough investigation into the spatial state variations of overhead lines in response to foundational changes, as well as alterations in the electrical distance between the conductor and both the ground and tower structures. These changes are crucial for maintaining the stability and safety of the power system. By establishing an appropriate coordinate system and analyzing how tower sinking affects the position of overhead lines, this study examines the combined effects of multiple factors on the position of overhead lines. These factors include the degree of tower sinking, the elasticity and tension of the overhead lines, the positions and heights of adjacent towers, wind force, temperature, and other environmental elements. A mathematical model was developed to describe the positional changes of overhead lines following tower sinkage, and formulas were used to calculate the new suspension point positions and electrical distance variations of the wires. In addition, the effects of wire oscillations due to wind forces on the electrical clearance at tower heads and the impact of insulator string deviation on wire stability and safety were analyzed. Finally, a series of measures were proposed to ensure the safe operation of the power system.